Upper extremity function in sprint vs. distance running - Hinrichs, R.; Froidman, A. (International Calgary Running Symposium, August 14-17, 2014, 2014)
In the 1980s Hinrichs and colleagues published a series of papers on upper extremity function in distance running. They found out that the arms contributed vertical (lift) but not to horizontal (drive) propulsion of the runner, reduced the horizontal excursion of the body center of mass (CM) both front-to-back and side-to-side, and most importantly, helped to balance the angular momentum of the legs about the vertical axis. While these papers provided an understanding of the function of the arms in running in general, there is enough difference between sprint running and distance running to warrant a re-examination. To this aim we collected 3D kinematic data from four video cameras of 10 collegiate sprinters running a simulated 100-m dash. We used methods similar to those Hinrichs used previously for distance runners. We found that the function of the arms is essentially the same for sprinters as for distance runners. However, in sprinting we found the arms contribute substantially more to lift than in distance running (about 25% vs. 5-7%). The arms still do not contribute to drive in sprinting, even when accelerating from the start. The reduction of side-to-side motion of the body CM still appears to be an important function of the arms, so a limited amount of cross-over of the arms in front or out to the side in back may be useful in sprint running.